Charlie y la fabrica de chocolate - Dahl, Roald; Blake, Quentin (Miami : Santillana, 2005)
Each of five children lucky enough to discover an entry ticket into Mr. Willy Wonka's mysterious chocolate factory takes advantage of the situation in his own way.
"Alfaguara."
Keywords: Chocolate candy -- Juvenile fiction; Wonka, Willy (Fictitious character) -- Juvenile fiction; Chocolate factories -- Juvenile fiction; Behavior -- Fiction; Spanish language materials; Humorous fiction